2017
DOI: 10.1038/s41598-017-16518-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the pheromone biosynthesis genes from the sex pheromone gland transcriptome of the diamondback moth, Plutella xylostella

Abstract: The diamondback moth was estimated to increase costs to the global agricultural economy as the global area increase of Brassica vegetable crops and oilseed rape. Sex pheromones traps are outstanding tools available in Integrated Pest Management for many years and provides an effective approach for DBM population monitoring and control. The ratio of two major sex pheromone compounds shows geographical variations. However, the limitation of our information in the DBM pheromone biosynthesis dampens our understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 84 publications
(91 reference statements)
3
16
0
Order By: Relevance
“…Herein, we identified a single PBANR in the S. insularis PG transcriptome that is 84% identical to Mamestra brassicae PBANR isoform B (ARO85772.1) and is very low in abundance (0.56 FPKM; Table 2 and S1 Text). The number of PBANR-encoding genes in the S. insularis PG was in accordance with Plutella xylostella [25], Agrotis segetum [58], and Agrotis ipsilon [59]. In addition, previous studies identified three isoforms of PBANR in Ostrinia nubilalis [60] and Mamestra brassicae [61].…”
Section: Pheromone Biosynthesis-activating Neuropeptide Receptor (Pbanr)supporting
confidence: 72%
See 1 more Smart Citation
“…Herein, we identified a single PBANR in the S. insularis PG transcriptome that is 84% identical to Mamestra brassicae PBANR isoform B (ARO85772.1) and is very low in abundance (0.56 FPKM; Table 2 and S1 Text). The number of PBANR-encoding genes in the S. insularis PG was in accordance with Plutella xylostella [25], Agrotis segetum [58], and Agrotis ipsilon [59]. In addition, previous studies identified three isoforms of PBANR in Ostrinia nubilalis [60] and Mamestra brassicae [61].…”
Section: Pheromone Biosynthesis-activating Neuropeptide Receptor (Pbanr)supporting
confidence: 72%
“…For instance, Δ9-desaturases have been divided into two groups: one with a substrate chain length preference of C16 >C18 (NPVE motif), and the other with a substrate chain length preference of C18 >C16 (KPSE motif) [22]. Subsequently, the unsaturated fatty acid is subjected to chain-shortening by β-oxidation, generating sex pheromone precursors of specific chain length [23], and the carbonyl carbon is modified to form an oxygenated functional group, such as an aldehyde, alcohol, or acetate ester, and these modifications involve some key biosynthesis enzymes; fatty acyl-CoA reductase (FAR) converts these acyl chains into fatty alcohols that act as actual sex pheromone components in various moths [24][25][26], but most fatty alcohols are either oxidized into the corresponding aldehyde by dehydrogenases [27][28] or esterified to form acetate esters by acetyltransferase (ATF) [29][30][31], resulting in the final functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…The target compound was obtained using column chromatography. (25)(26)(27)(28). These analogs were obtained from 1-hexadecanol (0.48 g, 2 mmol) or 1-hexadecanethiol (0.52 g, 2 mmol), 4-dimethylaminopyridine (0.01 g, 81.8 μmol), triethylamine (0.32 g, 3.2 mmol), and the corresponding anhydride using the synthetic method of 2.…”
Section: Saturated Carbamate Sex Pheromone Analogs (23 24)mentioning
confidence: 99%
“…Currently, most studies on sex pheromone analogs focus on their mechanism of action . As for P. xylostella , research mainly focuses on receptor protein and gene expression analysis for the synthesis and decomposition of sex pheromones . In this study, Z 11‐16: Ac and Hexadecyl acetate (16: Ac) were used as the parent structures and 23 sex pheromone analogs were designed and synthesized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation